Social aid of Covid-19 corruption: strategy and mitigation policy of Muhammadiyah East Java - Satria Unggul Wicaksana Prakasa; Achmad Hariri; Ida Nuriyah; Asis Asis; Idrus Salam (Legality : Jurnal Ilmiah Hukum, 2021)
This research underlines several problems related to the potential for corruption in social assistance (Bansos) provided by the Government through the allocation of the State Budget (APBN) and/or Regional Budget (APBD) to mitigate the economic impact and welfare of the community amid the Covid-19 pandemic. This research was intended to understand the role of Muhammadiyah as a civil society entity for the pattern of guarding the distribution of social assistance throughout East Java Province. The research approach used Participatory Action Research (PAR) and used socio-legal approach, which is an approach to control corruption based on community solidarity. The data collection was interviewed, FGD, and dissemination conducted online. Conclusions for this research are: (1). Corruption of the Covid-19 Social Assistance Agency is a serious threat and is detrimental to the Indonesian people who were severely affected by the pandemic, even though the Corruption Act has provided a serious threat to perpetrators of corruption committed during a disaster, with a maximum penalty of death; (2). The KPK-RI as the lead sector for corruption eradication in Indonesia can collaborate with various community groups on the agenda of eradicating corruption in Indonesia, especially the corruption of COVID-19 social Aid, through access to community-based reporting, and; (3). Participatory Action Research carried out by Muhammadiyah East Java residents is an effective step and a good example of how social entities are able to mitigate the potential for social assistance corruption of COVID-19 which is carried out both with a structural to cultural approach.